2011
DOI: 10.1080/17476930903394838
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic curvesP(x) −Q(y) = 0 and functional equations

Abstract: In this paper we give several conditions implying the irreducibility of the algebraic curve P (x)−Q(y) = 0, where P, Q are rational functions. We also apply the results obtained to the functional equations P (f ) = Q(g) and P (f ) = cP (g), where c ∈ C. For example, we show that for a generic pair of rational functions P, Q the first equation has no non-constant solutions f, g meromorphic on C whenever (deg P − 1)(deg Q − 1) ≥ 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…We refer the reader to Brockett (1983) for related work on Galois groups attached to linear feedback systems. Algebraic-geometric characterizations of decomposable rational functions in terms of root loci or associated Bezoutian curves have been obtained by Pakovich (2011).…”
Section: Notes and Referencesmentioning
confidence: 99%
“…We refer the reader to Brockett (1983) for related work on Galois groups attached to linear feedback systems. Algebraic-geometric characterizations of decomposable rational functions in terms of root loci or associated Bezoutian curves have been obtained by Pakovich (2011).…”
Section: Notes and Referencesmentioning
confidence: 99%
“…Several authors have studied functional equations of type f (a) = g(b), where f, g are given complex polynomials, which are to be solved in non-constant meromorphic complex functions a, b, and in particular the case when g(x) = c f (x) for some c ∈ C. Recently, Pakovich [23] studied the case when one allows f and g to be rational functions. To the study of such questions of importance are questions about reducibility of the curve 2 , and f 1 , f 2 , as well as g 1 , g 2 , have no common roots (that is the curve obtained by equating to zero the numerator of f (x) = g(y)), and reducibility of the curve (…”
Section: Remark 311mentioning
confidence: 99%
“…In the present paper, these are the critical values at simple critical points. Pakovich [23] showed that if f and g have at most one common critical value, then the corresponding curve is irreducible. He further showed that the curve…”
Section: Remark 311mentioning
confidence: 99%
See 1 more Smart Citation
“…Remark. As written, the proof of Theorem 1.2 relies on transcendental arguments via the results of [Pak11]. Nevertheless, I believe that it also holds in characteristic p > 0.…”
mentioning
confidence: 99%